Time to initiation of antenatal care visit and its predictors among reproductive age women in Ethiopia: Gompertz inverse Gaussian shared frailty model - Belay, Daniel Gashaneh; Alemu, Melaku Birhanu; Aragaw, Fantu Mamo; Asratie, Melaku Hunie (Frontiers in Global Women's Health, 2023)
Background Early initiation of antenatal care (ANC) is essential for the early detection of pregnancy-related problems and unfavorable pregnancy outcomes. However, a significant number of mothers do not initiate ANC at the recommended time. Therefore, this study aimed to determine the median time of ANC initiation and its predictors among reproductive-age women in Ethiopia. Methods We used the Ethiopian Demographic and Health Survey (EDHS) 2016 data set. The proportional hazard assumption was assessed using Schoenfeld residual test and log–log plot. A life table was used to determine the median survival time (time of ANC initiation). The Gompertz inverse Gaussian shared frailty model was the best-fitting model for identifying the predictors for the early initiation of ANC booking. Finally, the adjusted hazard ratio (AHR) with a 95% confidence interval (CI) was used to determine the significance of predictors. Results A total of 7,501 reproductive-aged women gave recent birth in the last 5 years preceding the survey. Nearly three in five women [61.95% (95% CI: 60.85–63.04%)] booked their first ANC visit with a median time of 4.4 months. Women who attended primary education (AHR = 1.10, 95% CI: 1.01–1.20), secondary and above (AHR = 1.26, 95% CI: 1.11–1.44), media exposure (AHR = 1.07, 95% CI: 1.00–1.16), rich wealthy (AHR = 1.17, 95% CI: 1.06–1.30), grand multiparous (AHR = 0.82, 95% CI: 0.72–0.93), unwanted pregnancy (AHR = 0.88, 95% CI: 0.81–0.96), small periphery region (AHR = 0.58, 95% CI: 0.51–0.67), and rural residence (AHR = 0.86, 95% CI: 0.75–0.99) were significantly associated with first ANC visit. Conclusion According to this study, a significant number of women missed their first ANC visit. The education status of women, place of residence, region, wealth index, media exposure, unintended pregnancy, and multi-parity were significantly associated with the time of initiation of the first ANC visit. Therefore, policymakers should focus on improving the socioeconomic status (education, media coverage, and wealth) of reproductive-aged women by prioritizing women who live in small periphery regions and rural residences to improve the early initiation of ANC.